Panax notoginseng Saponins Alleviate Coronary Artery Disease Through Hypermethylation of the miR-194-MAPK Pathway - Duan, Lian; Liu, Yongmei; Li, Jun; Zhang, Yun; Dong, Yan; Liu, Chao; Wang, Jie (Frontiers in Pharmacology, 2022)
Background: Panax notoginseng saponins (PNS) may have an inhibitory effect against coronary artery disease (CAD); however, the mechanism is unclear. Recently research has begun to evaluate the role of epigenetics in CAD. Our team found that hypomethylation of miR-194 could be an important mechanism of CAD. Purpose: The aim of this study was to investigate the effect of PNS against CAD and evaluate whether the mechanism is related to methylation of mi-R194. Methods: We conducted a randomized controlled trial with a double-blind placebo design on 84 patients with CAD. Treatment was continued for four weeks, and the clinical effect of PNS on CAD was observed. Methylation of miR-194, its promoter, and the key nodes of the MAPK pathway were measured by pyrosequencing and qRT-PCR. We then conducted a pharmacological analysis of the active components of PNS. The effects of PNS on oxidized human umbilical vein endothelial cells and the methylation of miR-194, its promoter, and the key nodes of the MAPK pathway were measured in vitro through methylation-specific PCR (MSPCR), qRT-PCR, western blot analysis, and Annexin V/propidium iodide apoptosis assay. Results: PNS improved symptoms of CAD. High-density lipoprotein and white blood cell counts demonstrated significant changes after treatment in the PNS group. No significant difference was observed between miR-194 and mRNA MAPK, FAS, RAS, and FOS in the PNS group after treatment. However, some notable trends were observed in these genes. The targets of PNS were predicted by the pharmacological components. Some targets were found to be differentially expressed genes in CAD sequencing. Six genes, including MAPK1, RAS, and FASL, were common targets of PNS in CAD sequencing. Correlations were observed between genes in the interaction network and clinical parameters. In vitro experiments confirmed that PNS could change the methylation of miR-194, its promoter, and MAPK, FAS, RAS, and FOS. Intervention with PNS is likely to improve apoptosis. Conclusion: We report the regulation of miR-194 promoter, miR-194, and MAPK methylation by PNS through cell experiments and a randomly controlled trial. PNS can be used for intervention in CAD by targeting the miR-194 promoter-miR-194-MAPK signaling pathway.